Partial Discharge Based Risk Assessment Framework for MV Switchgear Containing Electrical Defects - Hussain G.A.; Hassan W.; Mahmood F.; Kay J.A. (Institute of Electrical and Electronics Engineers Inc., 2024)
Partial discharge (PD) diagnostics is regarded as one of the powerful methods for the detection of potential electrical insulation defects in a medium voltage (MV) and high voltage (HV) switchgear. This article proposes a risk-based approach to identify the severity of several critical electrical defects in MV/ HV switchgear through PD testing. To accomplish this, several defects have been artificially created in a MV switchgear. The testing was carried out in the laboratory to investigate the characteristics of PD signals using D-dot sensor previously used and validated by the authors. Accordingly, the specific PD intensity of the discharge pulse has been considered as stress parameter and statistically modeled by an appropriate probability distribution. In this way, the probability of dielectric failure has been statistically quantified. The consequences of dielectric failure, and hence, the failure of the switchgear have been presented in terms of power outage cost and repair expenditures. The risk assessment is carried out by combing the probability of failure and its consequence. The estimated risk is an indication of the severity of the fault and can be specified as low, medium, high, or maximum. In this way, the proposed approach can be easily adopted by asset manager for risk assessment of switchgear in the petroleum and chemical industries. 1972-2012 IEEE.